Pengembangan Media Panggung Bercerita untuk Meningkatkan Kemampuan Bahasa Ekspresif Anak TK - Kunduri Kunduri; Iin Purnamasari; Muhtarom Muhtarom (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
The background that drives this research is the unavailability of media that supports children in improving expressive language skills of kindergarten children, children are less enthusiastic in participating in learning, it is necessary to increase children's expressive language skills so that learning becomes meaningful learning. The problems in this study are 1) how is the feasibility of storytelling stage media to improve children's expressive language skills?; 2) how is the practicality of storytelling stage media to improve children's expressive language skills?; 3) How is the effectiveness of storytelling stage media to improve children's expressive language skills? The objectives of this research and development are 1) to test the feasibility of storytelling stage media to improve children's expressive language skills; 2) testing the practicality of storytelling stage media to improve children's expressive language skills; 3) measuring the effectiveness of storytelling stage media to improve children's expressive language skills. This type of research is research and development by Borg & Gall. The population in this study were all children of group A TK Negeri Pembina Pekalongan City, which amounted to 13 children. The data in this study were obtained through documentation, interviews, questionnaires, and pretest and posttest of children's expressive language skills. The results of this study indicate that: (1) there are problems in the expressive language skills of kindergarten children, because learning is still one-way or learning is more teacher-centered; (2) development activities using procedures that produce storytelling stage media products that are valid, practical, effective, and suitable for use to improve children's expressive language skills; (3) the results of the validity test indicate that the developed media is valid to be used as an interactive and communicative learning medium; (4) the results of the effectiveness test show that children's expressive language skills using storytelling stage media are better than using conventional media such as books, posters, and pictures. This result is shown from the T-test calculation, where it is known that the value of Sig (2-tailed) is 0.000 <0.05. Based on the results of this study, it can be concluded that there are significant differences between the pretest and posttest data. The conclusion is that learning with storytelling stage media can improve the expressive language skills of Pekalongan City Pembina State Kindergarten children.